Pten ablation in adult dopaminergic neurons is neuroprotective in Parkinson's disease models - Domanskyi, Andrii; Geiβler, Christin; Vinnikov, Ilya A.; Alter, Heike; Schober, Andreas; Vogt, Miriam A.; Gass, Peter; Parlato, Rosanna; Schütz, Günther (The FASEB journal, 2011)
Parkinson's disease (PD) is a progressive age-related movement disorder that results primarily from the selective loss of midbrain dopaminergic (DA) neurons. Symptoms of PD can be induced by genetic mutations or by DA neuron-specific toxins. A specific ablation of an essential factor controlling ribosomal RNA transcription, TifIa, in adult mouse DA neurons represses mTOR signaling and leads to progressive neurodegeneration and PD-like phenotype. Using an inducible Cre system in adult mice, we show here that the specific ablation of Pten in adult mouse DA neurons leads to activation of mTOR pathway and is neuroprotective in genetic (TifIa deletion) and neurotoxin-induced (MPTP or 6OHDA) mouse models of PD. Adult mice with DA neuron-specific Pten deletion exhibit elevated expression of tyrosine hydroxylase, a rate-limiting enzyme in the dopamine biosynthesis pathway, associated with increased striatal dopamine content, and increased mRNA levels of Foxa2, Pitx3, En1, Nurr1, and Lmx1b—the essential factors for maintaining physiological functions of adult DA neurons. Pten deletion attenuates the loss of tyrosine hydroxylase-positive cells after 6OHDA treatment, restores striatal dopamine in TifIa-knockout and MPTP-treated mice, and rescues locomotor impairments caused by TifIa loss. Inhibition of Pten-dependent functions in adult DA neurons may represent a promising PD therapy.—Domanskyi, A., Geiβler, C., Vinnikov, I. A., Alter, H., Schober, A., Vogt, M. A., Gass, P., Parlato, R., Schütz, G. Pten ablation in adult dopaminergic neurons is neuroprotective in Parkinson's disease models. FASEB J. 25, 2898-2910 (2011). www.fasebj.org